2010
DOI: 10.1007/s10689-010-9372-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive BRCA1 and BRCA2 mutation analyses and review of French Canadian families with at least three cases of breast cancer

Abstract: Few studies have reported on the comprehensive BRCA1/2 mutation analyses of hereditary breast cancer (HBC) families of French Canadian descent. Here we report the investigation of 82 families with at least 3 cases of breast cancer evaluated for mutations by DNA sequencing and/or multiplex ligation-dependent probe amplification (MLPA) assay. DNA sequencing identified pathogenic mutations in 37 (45.1%) families, of which 70.2% were one of three recurring mutations (BRCA1:R1443X, BRCA2:8765delAG, and BRCA2:E1953X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 48 publications
5
39
1
Order By: Relevance
“…In total, ~0.4% of the same cohort of breast cancer cases not selected for a family history of cancer, and who were also analyzed for the presence of recurrent BRCA1/BRCA2 mutations, were identified to be PALB2:c.2323C>T [p.Q775X] carriers, whereas no carriers were observed among newborns (7). These results are consistent with those of previous studies, which reported that ~40 and 1% of French Canadian breast cancer and breast-ovarian cancer families harbor germline BRCA1/BRCA2 or PALB2 germline mutations, respectively (2,3,8,9).…”
Section: Introductionsupporting
confidence: 88%
“…In total, ~0.4% of the same cohort of breast cancer cases not selected for a family history of cancer, and who were also analyzed for the presence of recurrent BRCA1/BRCA2 mutations, were identified to be PALB2:c.2323C>T [p.Q775X] carriers, whereas no carriers were observed among newborns (7). These results are consistent with those of previous studies, which reported that ~40 and 1% of French Canadian breast cancer and breast-ovarian cancer families harbor germline BRCA1/BRCA2 or PALB2 germline mutations, respectively (2,3,8,9).…”
Section: Introductionsupporting
confidence: 88%
“…Loss of function of BRCA by mutations might lead to abnormal cell cycle and cell growth, and then cancers. Our result in this study shown the rate of BRCA1 gene mutation is 52.54% among familiar breast cancer patients, which is higher than published result (11). A possible reason is that invasive ductal carcinoma is the main histopathologic types of breast cancer in this cohort of patients, in which the mutation rates in BRCA1 even as high as 74.19%.…”
Section: Discussioncontrasting
confidence: 64%
“…Most subjects with pdac were white (79.2% maternal, 80.1% paternal), with an enrichment of cases (37.4%) having French-Canadian ancestry (at least 1 parental origin, Table iii). In addition, 56.8% of pdac-affected subjects had an ancestry (that is, French-Canadian, Ashkenazi Jewish, Greek, German, Polish, or Latvian) known to harbour recurrent germline ("founder") mutations in the BRCA1, BRCA2, and PALB2 pdac predisposing genes (Table iii) [11][12][13][14][15][16][17][18][19] . Table iii also shows data describing education, environmental exposures, weight loss, and history of type 2 diabetes and pancreatitis for enrolled patients with pdac.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, more than half the enrolled patients in the qpcs affected with pdac (56.8%) had an ancestry (at least 1 parental origin) known to harbour founder BRCA1 and BRCA2 mutations [11][12][13][14][15][16][17][18][19] . The founder populations represent a genetically enriched subgroup ideal for gene discovery studies 8,[37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation